Factors Affecting Intention to Use Online Dating Sites in Malaysia - Alam, Syed Shah; Islam, Md. Rabiul; Mokhbul, Zafir Khan Mohd; Makmor, Nurkhalida Binti (International Journal of Engineering and Technology, 2018)
Online dating communities have great market potential; therefore, understanding the perceptions of young generation of the factors influencing their intention to use such site is vital. This research examined five key dimensions of intention to use online dating communities in Malaysia based on some information system theories. Research model for this study was developed based on the literature on information system research. This study was adopted convenient sampling of non-probability sampling procedure. Data were collected through self-administered questionnaire and multiple linear regression was used to analyze data. The findings of the study show that word-of-mouth, attitude, perceived enjoyment and perceived playfulness are key determinants of young adults’ intention to use online dating sites. However, there is no significant relationship between trust and intention to use online dating sites. This research can serve as a starting point for online dating research, while encouraging further exploration and integration addition adoption constructs. Other business agencies should create better awareness of the usage of online dating sites. As Malaysian are choosing their own pair for their family life, so this finding gives some insight to the young generation of Malaysia to focus on finding their own partners from online sites.